Progress in risk factors of diabetic macular edema - Xiao-Juan Su (Guoji Yanke Zazhi, 2022)
Diabetic macular edema(DME)is a severe ocular complication of diabetes and one of the leading causes of vision loss in diabetic patients. The pathogenesis of DME is complicated, and the key to treatment is controlling the systemic factors that cause the deterioration of DME. The existing studies have shown that the increased risk of DME is related to many factors. In this paper, the risk factors of DME were reviewed to provide theoretical support for the research and prevention of DME.